PENERAPAN METODE KOOPERATIF TIPE ROUND TABLE DALAM MENINGKATKAN KETERAMPILAN MENULIS PUISI PADA SISWA KELAS VIII SMPN I SLEMAN - Pradana Putu, Octavian Muning, dan Nur Wulansari (Pelita - Jurnal Penelitian Mahasiswa UNY, 2008)
This research is aimed at describing the improvement of the ability in writingpoem for students of SMPN I Grade VIII Sleman Yogyakarta in the learning ofIndonesian language and culture through the implementation of cooperative learningmodel of round table type.The subjects of the research were students of SMPN 1 Grade VIII SlemanYogyakarta in the academic year 2007/2008. This is a classroom action research. Theprocess of conducting this research was divided into two cycles. In these two cycles, theimplementation of cooperative learning model was applied twice. This research appliedunstructured observation, meaning that observation was not limited in certainframework. In the reflection phase, the researcher and collaborator tried to understandthe process, problem, and obstacle during the treatment. The techniques of collectingdata were test, questionnaire, interview, observation, and documentation of learningactivity. Meanwhile, the analysis of the data was done by employing a descriptive –qualitative and descriptive statistic technique.The result of the research shows that the use of cooperative learning model ofround table type can improve the students’ ability in writing poems.The students’scompetence before getting the treatment is in fair category. It can be seen from the pretest,that is 4.18. However, after they are given treatments twice, the students’ abilityimprove. It is shown by the score in the second cycle. From this result, it can beconcluded that there is an improvement on the students’ ability in writing poem for 2.32point.Key words: round table type, writing poem, cooperative learning